Сучасна грузинська компаративістика: напрямки досліджень, проблеми - Грицик, Л.; Мчеделадзе, І. (Слово і Час, 2021)
У статті простежено розвиток грузинської компаративістики другої половини ХX — початку ХХІ ст., її матеріал, головні напрямки
досліджень та основні проблеми. Показано, як зміщуються акценти
із традиційного вивчення грузинсько-російських взаємин у радянський
період до грузинсько-європейсько-східних у постколоніальну епоху; як
відбувається оновлення методологічних підходів і зміна просторового
поля компаративних студій. Осмислено місце грузинсько-українських
порівняльних досліджень у контексті розвитку сучасної грузинської
науки. Розглянуто праці представників новітнього грузинського порівняльного літературознавства, діяльність Асоціації компаративістів
Грузії та Інституту порівняльного літературознавства Тбіліського
університету. Taking into account the factual material, research methods, and tasks, the authors trace
the evolution/changes in Georgian comparative studies. It is notable that typological approaches,
along with contact-genetic ones, are now actively used. These changes become
firmly established due to the studies of iconic figures and periods, which attract the special
attention of the scholars. Eurocentric concepts give place to other ones that have their basis
in the study of the national literature and include philosophical, anthropological, psychological,
and religious factors in the field of research. A lot of attention has been given to the
principles of selecting literary texts for translation.
The field of Georgian comparative studies has been remarkably changed/updated in
the late 20th — early 21st centuries. Along with historians of literature, the theorists, critics,
translators, and specialists in European and Oriental languages have been involved, which
affected the level of comparative studies. Among the raised issues are reception, imagology,
typology of anti-colonial narratives, genre transformations, postmodern discourse, etc. The
character of Georgian-Ukrainian comparative studies changed drastically: it is obvious in
the approaches/assessments of literary translation and in all connecting issues in general.
Comparative studies came as close as possible to the theory of literature, which let the researchers
(R. Khvedelidze, N. Naskidashvili, S. Chkhatarashvili, I. Mchedeladze) update the
methodology and intensify their work on the different levels of research, regardless of the
presence/absence of contexts.
The present surge in Georgian comparative studies started in the 2010s. It is connected
to the organization of effective specialized research centers. Of great interest are the comparative
studies aiming to show the history of Georgian literature as an individual version of
the world literature (I. Ratiani), to identify the features of the Georgian literary canon based
on the three main literary models (Middle Ages, Romanticism, post-Soviet), with a focus on
the combination of ‘canonical’ and ‘non-canonical’ in innovative writing.